Improvement of thermal‐type MEMS flow sensor chip via new process of silicon etching with sacrificial polycrystalline silicon layer. Issue 4 (25th October 2021) - Kasai, Takashi; Momotani, Koji; Nakano, Yu; Nakao, Hideyuki
Abstract: This paper reports upon a new process for the flow sensor fabrication of a thermal microelectromechanical systems (MEMS) and its performance improvement. A unique feature of the proposed process is the silicon etching, which is a combination of normal crystal‐oriented silicon etching and isotropic etching of polycrystalline silicon (poly‐Si). The poly‐Si layer works as a sacrificial layer and promotes etching of the silicon substrate in the horizonal direction, thereby enabling location of the etching holes in the membrane of the flow sensor without the conventional etching rules. Some designs for the flow sensors, which have been infeasible with normal processes, were thus fabricated and evaluated. Hence, the new process improves the design flexibility of the membrane and enhances flow sensor performance, such as 38.3% reduction in power consumption.